Magnetic resonance T1ρ quantification of human brain at 5.0 T: A pilot study - Liu, Yuanyuan; Wang, Wenxin; Zheng, Yijia; Wang, Haifeng; Zheng, Hairong; Liang, Dong; Zhu, Yanjie (Frontiers in Physics, 2022)
MR quantitative T1ρ mapping has gained increasing attention due to its capability to study low-frequency motional processes and chemical exchange in biological tissues. At ultra-high fields, the chemical exchange and proton diffusion in biological tissues should be more prominent. In this study, for the first time, we aim to test the feasibility of brain T1ρ mapping at 5.0 T MR scanner and compare the T1ρ values estimated using 3.0 T and 5.0 T scanners. Preliminary experimental results show that 5.0 T achieves T1ρ-weighted images with a higher signal-to-noise ratio than those acquired at 3.0T. The SNR benefit at 5.0 T is more obvious in high-resolution imaging. The T1ρ quantifications at 5.0 T are: Corpus callosum (67.4±1.9 ms), Corona radiate (71.5±1.8 ms), Superior frontal gyrus (67.6±2.5 ms), Putamen (58.9±1.2 ms), Centrum semiovale (84.0±6.3 ms). Statistical analysis results indicate that the T1ρ values at 5.0 T show no significant difference with those obtained at 3.0 T (all P >0.05). The interﬁeld agreements in terms of T1ρ values between 3.0 T and 5.0 T were substantial (all ICCs >0.7). The coefficients of variation for T1ρ measurements from 3.0 T and 5.0 T were all less than 6.50% (2.28%–6.32%).